PENGARUH LATIHAN JUMP HEADER UNTUK MENINGKATKAN KETERAMPILAN HEADING PADA TIM SEKOLAH SEPAK BOLA BINA BAKAT U-15 PEKANBARU - Effendi, Yusuf; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based of the observation has done the researcher in the yard on the activity process learning the heading material, the researcher seen problems stated less and low from technique football, they are : the ball did not move to they aim, because the less power jump heading, based on problem the researcher want to give method at school Bina Bakat U-15. The purpose of the researcher to increase heading technique playing football. They are : Jump and heading ball did not move, Direction jump to group frinds, racing jump header, throw driction and catch ball, the kind of this research is expriment to seen effect jumping header training. The purpose of the research want to see effect jumping header training to increase skill heading to team school footlball Bina Bakat U-15 Pekanbaru. Sum 20 students. Base this data is used completely population to become xample. Base this date has found from pre-test and post-test. Instrument has done research is test. Playing ball with heading as instrument to measure heading heading skill. Analysis has done the used test. Based on analysis data and discussio, as evidenced by thitung 9 and ttabel 1,792. Means thitung> ttabel At some level ɑ = 0.05. then can be concluded that there is significant influence from jump training to improve the skills of heading on the school footlball team Bina Bakat U-15 Pekanbaru. Key Words: Exercise Jump Header, Heading Ability, Football.